Real-time sonoelastography findings in a patient with tennis leg: A promising technique in the assessment of muscle rupture - Koçyiğit, Figen; Kuyucu, Ersin; Koçyiğit, Ali (Edizioni Minerva Medica, 2016)
[Abstract Not Available]
WOS: 000399965500017
Keywords: Physical and Rehabilitation Medicine; Injections; Musculoskeletal Ultrasound